INDUSTRIALIZATION AND DE-INDUSTRIALIZATION IN INDONESIA 1983-2008: A KALDORIAN APPROACH - D.S. Priyarsono; Titi Kanti Lestari; Diah Ananta Dewi (Journal of Indonesian Economy and Business (JIEB), 2010)
Economists have for a long time discussed the causes of economic growth and the mechanisms behind it. Kaldor viewed advanced economies as having a dual nature verysimilar to that of developing countries, with an agricultural sector with low productivity and surplus labour, and a capital intensive industrial sector characterized by rapid technical change and increasing returns. The transfer of labour resources from the agricultural sector to the industrial sector depends on the growth of the latter’s derived demand for labour. With this background this study attempts to show the periods when the Indonesian economy indicated the processes of industrialization and deindustrialization. Italso attempts to identify whether the economy experienced positive deindustrialization (i.e., showed signs of economic maturity where service sector substituted the role of industrial sector as the engine of growth) or negative deindustrialization (i.e., showed signs of economic stagnancy where industrial sector could not grow rapidly enough to absorb surplus labour from agricultural sector). Lastly, this study attemps to analyze several factors that might be responsible for the process of the deindustrialization.Keywords: industrialization, deindustrialization, economic growth